2002
DOI: 10.3732/ajb.89.8.1189
|View full text |Cite
|
Sign up to set email alerts
|

Root starch storage and allocation patterns in seeder and resprouter seedlings of two Cape Erica (Ericaceae) species

Abstract: Post-fire sprouting of dormant buds in resprouter plants is facilitated by stored carbohydrate reserves, with starch being the critical reserve. Starch is mainly stored in xylem parenchyma ray tissue of woody underground organs, such as burls, lignotubers, and roots. We carried out a comparative analysis of the pattern of starch storage and the proportion of parenchymatic ray tissue in the upper root or cotyledonary region of seedlings from seeder and resprouter forms within two Cape Erica (Ericaceae) species:… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
72
0

Year Published

2009
2009
2018
2018

Publication Types

Select...
7
1
1

Relationship

0
9

Authors

Journals

citations
Cited by 93 publications
(76 citation statements)
references
References 37 publications
4
72
0
Order By: Relevance
“…most branches emerging from the main axis) is expected in plants developing roots that function as storage organs or to obtain deep resources . Thick storage roots, like those of R+, tend to have more parenchymatic cells and consequently higher storage capacity, which is developed early in seedling ontogeny (Verdaguer and Ojeda 2002). However, thick roots have low surface:volume ratio (SVR) and offer higher resistance to the radial flow of water, both causing lower root absorption potential (Larcher 1995;Huang and Eissenstat 2000).…”
Section: Discussionmentioning
confidence: 99%
“…most branches emerging from the main axis) is expected in plants developing roots that function as storage organs or to obtain deep resources . Thick storage roots, like those of R+, tend to have more parenchymatic cells and consequently higher storage capacity, which is developed early in seedling ontogeny (Verdaguer and Ojeda 2002). However, thick roots have low surface:volume ratio (SVR) and offer higher resistance to the radial flow of water, both causing lower root absorption potential (Larcher 1995;Huang and Eissenstat 2000).…”
Section: Discussionmentioning
confidence: 99%
“…Resprouting in trees after low but pervasive levels of disturbance is supported by both below-and aboveground reserves, whereas resprouting in shrubs and trees subject to frequent, severe disturbance is supported by belowground reserves (93). Mediterranean woody shrubs in fire-prone heathlands allocate and accumulate more NSC belowground than sympatric, obligate seeders do (6,58,140). Here, starch reserves have been identified as critical for resprouting and are stored in xylem parenchyma ray tissue of woody underground organs, such as burls, lignotubers, and roots (6,140).…”
Section: Relationships To Demographic Processesmentioning
confidence: 99%
“…Mediterranean woody shrubs in fire-prone heathlands allocate and accumulate more NSC belowground than sympatric, obligate seeders do (6,58,140). Here, starch reserves have been identified as critical for resprouting and are stored in xylem parenchyma ray tissue of woody underground organs, such as burls, lignotubers, and roots (6,140). Similarly, savanna trees, which persist through repeated top kill by resprouting, also store large amounts of NSC (e.g., sugars plus starch = 28-30% mass) belowground in specialized organs (i.e., lignotubers) (49,144).…”
Section: Relationships To Demographic Processesmentioning
confidence: 99%
“…Species show different aboveground and belowground characteristics responsible for their survival, growth, and reproduction in different habitats. There is broad evidence supporting a correspondence between the various root system traits developed by species in drought-prone ecosystems and their performance (Davis et al 1999;Bell 2001;Verdaguer and Ojeda 2002), with important implications on the extent of fluctuations in water status of species (Fleck et al 1995(Fleck et al , 1998. In addition, it has been reported that the first summer rainless period after seedling establishment is a major limiting factor when seedling roots are not fully developed (Vallejo et al 1999;Pratt et al 2007).…”
Section: Introductionmentioning
confidence: 99%